Pengembangan Alat Ukur Kreativitas Pada Mahasiswa Jurusan Teknik Arsitektur - Yeni Anna Appulembang; P. Tommy Y.S. Suyasa (Fakultas Psikologi Universitas Tarumanagara, 2014)
Creativity is very important in all fields, Architecture is one of them because architecture is the art and technique of designing the enclosure of space for human use. The architect must be creative and capable of thinking, feeling and convey spatial ideas. Therefore more important to measure their ability on creativity for applicant’s architecture student when the process entrance examinations. The purpose of research is to develop an instrument to measure the creativity architecture students. In this research, the researcher was using quantitative method. A total of participants 275 . Percentile rank norm was utilized to determine creativity architecture students. In this research were measure content validity, construct validity and internal consistency reliability. To measure content validity, researcher was given the instrument to five panel of expert. Internal consistency reliability was 0.8. The research results in the form of instruments to measure creativity architecture students. The results are then used as a means of used to selecting students applying for the architecture study program.Keywords : architecture, creativity